2020
DOI: 10.1002/pat.5171
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermal, and dielectric properties of porous PVDF/Li4Ti5O12 nanocomposite membranes for high‐power lithium‐polymer batteries

Abstract: Polymer nanocomposites consisting of materials such as ionic polymers and nano‐ceramic fillers are widely used in high‐power lithium‐polymer batteries because of their high ionic conductivity, good mechanical strength, electrothermal stability, and better compatibility with electrodes. Nanocomposite films of polyvinylidene fluoride (PVDF)/lithium titanium oxide Li4Ti5O12 (LTO) with different volume fractions of LTO nanoparticles (NPs) are prepared via casting method. The DSC thermograms revealed a slight decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…As a result of fitting the curves in Figure 11A, the equivalent circuit model's parameters are listed in Table 3. Results show that bulk resistance R b decreases as TiO 2 NPs concentration increases, indicating a greater number of connected conductive channels 71 . The reason for this decrease in Rb might be because of both the increase in the content of charge carriers and the decrease in the crystallinity level of the samples.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As a result of fitting the curves in Figure 11A, the equivalent circuit model's parameters are listed in Table 3. Results show that bulk resistance R b decreases as TiO 2 NPs concentration increases, indicating a greater number of connected conductive channels 71 . The reason for this decrease in Rb might be because of both the increase in the content of charge carriers and the decrease in the crystallinity level of the samples.…”
Section: Resultsmentioning
confidence: 93%
“…Results show that bulk resistance R b decreases as TiO 2 NPs concentration increases, indicating a greater number of connected conductive channels. 71 The reason for this decrease in Rb might be because of both the increase in the content of charge carriers and the decrease in the crystallinity level of the samples. Additionally, bulk capacitance values (Q) rise with increasing TiO 2 NPs concentration, which can be explained by the previous description of the production of many nanocapacitors.…”
Section: Complex Impedancementioning
confidence: 99%
“…The dielectric constants are 9.0, 9.4, 12.9, and 9.7, respectively, for the samples PVK0, PVK2.5, PVK5, and PVK7.5 at a field frequency of 40 Hz (Figure a). It has been found that the DC is maximum at 40 Hz and decreases with increasing frequency . In reality, any semiconductive sample has conductive grains surrounded by insulating grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, most polymers have a lower dielectric constant despite the presence of ion pairs when the dielectric measurements are performed. The dielectric characteristics includes the real e¢ and imaginary e¢ ¢ components of the complex permittivity e* which is given by the equation [72]: ( )…”
Section: Dielectric Behavior and Ac Electrical Conductivitymentioning
confidence: 99%